Property, tenancy and urban growth in Stockholm and Berlin, 1860 - 1920. - Forsell, Hakan (Routledge, 2018)
From the middle of the nineteenth century, most European cities experienced a period of unrivalled growth and development that forever changed not only their physical characteristics, but also their social foundations. As the great industrial cites were forced to face the new and unprecedented challenges of rapid urbanisation and increased population, they had to rethink many of the concepts on which previous city institutions had been based. One of the most fundamental of these was the role of house ownership, and the rights and responsibilities it offered. Exploring the social and political meanings attributed to property - specifically home ownership - this study looks at how these changed during the course of the modern city building process between 1860 and 1920. Focussing on two northern European capital cities, Berlin and Stockholm, it provides a symmetrical investigation that helps illuminate the competing factors that shaped the shifting nature of cityscapes and urban social structures.
Keywords: Stadtgeschichte; Stadtbaugeschichte; Internationaler Vergleich; Stadtforschung; Stadtwachstum; Bevölkerungswachstum; Grundeigentum; Eigentümer; Hausbesitz; Liberalismus; Stadtverwaltung; Kommunale Selbstverwaltung; Regulierung; Stadtplanung; Städtebau; Wohnungsbau; Mietwohnungsbau; Mietskaserne; Wohnungsfrage; Mietrecht